Do Women Ask? - Benjamin Artz; Amanda H. Goodall; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2016)
Women typically earn less than men. The reasons are not fully understood. Previous studies argue that this may be because (i) women 'don't ask' and (ii) the reason they fail to ask is out of concern for the quality of their relationships at work. This account is difficult to assess with standard labor-economics data sets. Hence we examine direct survey evidence. Using matched employer-employee data from 2013-14, the paper finds that the women-don't-ask account is incorrect. Once an hours-of-work variable is included in 'asking' equations, hypotheses (i) and (ii) can be rejected. Women do ask. However, women do not get.
Keywords: J31; J71; 330; matched employer-employee data; female discrimination; wages; gender